The frequency of coffee consumption in the Slavic population and its impact on health - Czchowski, Konrad; Kościołek, Aleksandra; Misiak, Jakub; Kościołek, Dawid; Kępczyk, Martyna; Ojdana, Miłosz; Urbaś, Michał; Surowiecka, Kaja; Szalbot, Konrad; Tokarski, Mikołaj (Journal of Education, Health and Sport, 2024)
Introduction and purpose: There are many articles specifying coffee's influence on the health and behavior of consumers. However, most of the studies are conducted on populations living in the United States, Western Europe or China. We did not find many studies reporting the effects of coffee consumption on the Slavic population. The aim of our study was to determine the frequency of coffee consumption in this population and its impact on such health elements as insomnia, body weight, well-being, irritation, hypertension or headache. Material and method: The anonymous survey included questions about the frequency of coffee consumption and selected health effects was created and subsequently distributed through social media (Telegram platform) in August 2023. Results: We collected a total of 89 surveys. The median age of participants was 31 (IQR: 24-38). 27 individuals indicated that they do not consume coffee at all (30.34%). The rest of the group most often choose the following options: I drink it several times a day - 24 individuals (26.97%) and 26 individuals drink it once a day (29.21%). We demonstrated a correlation between the amount of coffee consumption and the frequency of insomnia (r=0.39, p=0.028). Additionally, we observed a negative correlation between coffee consumption and body weight (r=0.18, p=0.048). However, we did not find a relationship between coffee consumption and elevated or lowered mood (p>0.05). Conclusions: In the study group, the frequency of coffee consumption was higher than the global average and in some cases led to insomnia. The positive aspects of drinking coffee outweighed the side effects and lead to the conclusion that it is a safe drink in the group of surveyed Slavs.